Lycopene prevents non-alcoholic fatty liver disease through regulating hepatic NF-κB/NLRP3 inflammasome pathway and intestinal microbiota in mice fed with high-fat and high-fructose diet - Gao, Xiang; Zhao, Xia; Liu, Min; Zhao, Huimin; Sun, Yongye (Frontiers in Nutrition, 2023)
Lycopene (LY) belongs to carotenoids and is abundant in red fruits and vegetables. Several previous studies suggested that LY is beneficial for ameliorating non-alcoholic fatty liver disease (NAFLD), while the potential mechanisms are unclear. The present study aimed to clarify the potential mechanisms of LY in preventing NAFLD via exploring the hepatic NF-κB/NLRP3 inflammasome pathway and intestinal microbiota composition in high-fat and high-fructose diet (HFFD)-fed mice. Fifty eight-week-old male C57BL/6J mice were randomly assigned into 5 groups: Normal control group (NC); HFFD group; HFFD with low dose of lycopene group (LLY, 20 mg/kg/d); HFFD with high dose of lycopene group (HLY, 60 mg/kg/d) and HFFD with resveratrol group (RSV, 50 mg/kg/d, positive control). After 8 weeks, feces were collected and the 12 hours fasted mice were sacrificed to acquire tissues and blood for parameters measurement. The results showed that the mice in LLY, HLY and RSV groups had significantly lower body weight gain, weight of white adipose tissue, serum levels of high density lipoprotein-cholesterol (HDL-C), low density lipoprotein-cholesterol (LDL-C), lipopolysaccharide (LPS), alanine aminotransferase (ALT), and hepatic concentrations of triglyceride (TG) and interleukin-6 (IL-6) than that in the HFFD group (p < 0.05). HLY and RSV groups also displayed lower serum levels of TG, total cholesterol (TC) and hepatic levels of tumor necrosis factor-α (TNF-α) than the HFFD group (p < 0.05). Liver protein expressions of NLRP3, Pro-Caspase-1, Caspase-1 and NF-κB were lower in the LLY, HLY and RSV groups than those in the HFFD group (p < 0.05). The feces of LY -treated mice had higher relative levels of SCFAs producing bacteria Allobaculum and lower destructive bacteria, including Firmicutes, Lachnospiraceae_NK4A136_group, Desulfovibrio and Alistipes over the HFFD group (p < 0.05). RSV group also displayed lower fecal levels of Lachnospiraceae_NK4A136_group, Desulfovibrio and Alistipes than the HFFD group (p < 0.05). In conclusion, LY might prevent NAFLD by suppressing hepatic NF-κB/NLRP3 inflammasome pathway and attenuating gut microbiota dysbiosis.